2017
DOI: 10.1175/jas-d-16-0362.1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Precipitation in Controlling the Transition from Stratocumulus to Cumulus Clouds in a Northern Hemisphere Cold-Air Outbreak

Abstract: Aircraft observations in a cold-air outbreak to the north of the United Kingdom are used to examine the boundary layer and cloud properties in an overcast mixed-phase stratocumulus cloud layer and across the transition to more broken open-cellular convection. The stratocumulus cloud is primarily composed of liquid drops with small concentrations of ice particles and there is a switch to more glaciated conditions in the shallow cumulus clouds downwind. The rapid change in cloud morphology is accompanied by enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
152
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(214 citation statements)
references
References 57 publications
22
152
0
2
Order By: Relevance
“…Generally, our results support findings by Abel et al (2017) in the sense that ice processes induce a cloud deck thinning and a breakup in organization. Conceptually, we show that cloud ice strengthens subcloud precipitation through sedimenting snow, ice, and graupel (as summarized in Figure 4).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Generally, our results support findings by Abel et al (2017) in the sense that ice processes induce a cloud deck thinning and a breakup in organization. Conceptually, we show that cloud ice strengthens subcloud precipitation through sedimenting snow, ice, and graupel (as summarized in Figure 4).…”
Section: Discussionsupporting
confidence: 91%
“…However, their aerosol concentrations are much larger than observed for the Arctic environment and in deep convective clouds latent heating from condensation and turbulence are stronger than in shallow stratocumulus. Moreover, the impact of prognostic CCN, where collision-coalescence and sedimentation processes can clean out the boundary layer (Abel et al, 2017;Wood et al, 2008) should be investigated in more detail. Generally, our results agree with their study, but we find a shorter-term response in cloud base precipitation intensity and cell size induced by CCN concentration changes as opposed to ice phase processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S3-S5). Observational studies of Arctic mixed-phase marine Sc (Young et al, 2016) and North Atlantic CAOs (Abel et al, 2017) have previously reported precipitation as snow below cloud with little rain measured, indicating that our idealised study is in broad agreement with measurements in this region.…”
Section: Test 1: Stable Stratocumulussupporting
confidence: 84%